2013
DOI: 10.1645/12-99.1
|View full text |Cite
|
Sign up to set email alerts
|

Proterometra macrostoma(Trematoda: Azygiidae): Location of the Redia and Emergence Path from the Snail,Elimia semicarinata(Gastropoda: Pleuroceridae)

Abstract: The objectives of this study were to describe (1) the osmotic environment and precise location of the Proterometra macrostoma redia in its snail intermediate host, (2) where retraction of the distome body into the cercarial tail occurs, and (3) the subsequent emergence path of the cercaria out of the snail. Snails, Elimia semicarinata , were collected from North Elkhorn Creek in Scott County, Kentucky and screened daily for patent infections. Live rediae were extracted from infected snails in either artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This makes the assessment of operational taxonomic units based on cercarial morphology alone challenging, especially given the low number of reported diagnostic characteristics. Various workers have treated morphology, behavior, and host-parasite relationships of the cercariae [13,[6][7][8][9][10][11][12]33,[66][67][68][69][70][71][72], development and morphology of the eggs [35,73] and adults [1,6,15,[21][22][23][24][25]28,33,35], and general attributes of the intra-molluscan stages, sporocyst and redia [11,14,74]. Moreover, 8 cercarial strains of P. macrostoma have been morphologically characterized from Lake Erie [13], Kentucky [8,75], Michigan [8], and Ohio [8].…”
Section: Molecular Datamentioning
confidence: 99%
“…This makes the assessment of operational taxonomic units based on cercarial morphology alone challenging, especially given the low number of reported diagnostic characteristics. Various workers have treated morphology, behavior, and host-parasite relationships of the cercariae [13,[6][7][8][9][10][11][12]33,[66][67][68][69][70][71][72], development and morphology of the eggs [35,73] and adults [1,6,15,[21][22][23][24][25]28,33,35], and general attributes of the intra-molluscan stages, sporocyst and redia [11,14,74]. Moreover, 8 cercarial strains of P. macrostoma have been morphologically characterized from Lake Erie [13], Kentucky [8,75], Michigan [8], and Ohio [8].…”
Section: Molecular Datamentioning
confidence: 99%
“…One figure from that study showed a cercaria emerging from the tissues of the snail, but no attempts were made to determine the relative importance of the anterior tissues in the shedding process. More recent studies in other trematode systems (Oates and Fingerut, 2011;Rosen et al, 2013) have also described cercarial emergence from anterior tissues of snails. These studies have all agreed that cercariae can emerge from several tissues, and those involved seem to be the mantle collar, headfoot, anus, and pseudobranch.…”
mentioning
confidence: 94%